The effect of soothing sound machines and meditation using CD players on relaxation in acute care orthopedic patients - Barbara Bauer; Carolyn Mitchell; Erin Salmon (The Beryl Institute, 2015)
This research studied the relaxation effect in orthopedic surgical patients using guided meditation or soothing sounds (SS) machines. The study used a comparative study design to evaluate differences in the effect of SS or guided meditation on patients' perceptions of relaxation. IRB approval was obtained prior to initiating the study. A convenience sample of orthopedic surgery patients consented to voluntarily rate their perceptions of relaxation on a 5-point Likert scale ranging from "none", "mild", "moderate", "good" or "very good". A demographic survey was used to describe the sample. The sample included 50 patients with ages ranging from 40 to 70 years. Seventy-eight percent (78%) of the sample was female and 22% were male. The participant selection of relaxation type was 82% soothing sounds machines, meditation 12%, and both (SS machines and meditation) 6%. The response rate was 100% for the guided meditation as compared to the 93% response rate for the SS machine. The greatest relaxation change was noted for the guided meditation (66.5% good to very good) as compared to the SS machines (63.5% good to very good). Both SS machines and guided meditation improved relaxation with greater than 82% rating moderate to very good change. More patients selected SS machines over guided meditation. The active process for guided meditation provided a higher relaxation rating than the passive process using soothing sounds machines.